What drives employee performance? Revisiting the human performance system model - Intan Soraya Rosdi,; Mazni Alias,; Norhazlin Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The performance of firms is a result of the work performance of its individual employees making up its valuable workforce. While there exist several research models offering their perspectives of work performance factors, the human performance system model offers a relatively more detailed and comprehensive range of determinants of individual work performance. However, empirical evidence for the model seems absent from literature and qualitative evidence seems scant and only limited to a few case studies. The minimal evidence suggests that this area is still in need of exploration. Hence, this paper explores the constructs in the human performance system model from qualitative data through focus group discussion sessions on factors determining individual work performance. The model’s six work performance factors are performance specification, task support, consequences, feedback, skills/knowledge, and individual capacity. Data comes from 280 research participants engaged through 33 focus group discussion sessions. The results are consistent with the work performance factors proposed by the human performance system model. Besides lending support to the human performance system model, another important contribution of the study is the identification of research variables, which can be used for the development of a survey questionnaire for future empirical testing of the model.